Characterizing how acidic pH conditions affect the membrane-disruptive activities of lauric acid and glycerol monolaurate - Valle-González, Elba Ruth (2020)
Fatty acids and monoglycerides are single-chain lipid amphiphiles that interact with phospholipid membranes as part of various biological activities. For example, they can exhibit membrane-disruptive behavior against microbial pathogens on the human skin surface. Supported lipid bilayers (SLBs) provide a useful experimental platform to characterize these membrane-disruptive behaviors, although related studies have been limited to neutral pH conditions. Herein, we investigated how lauric acid (LA) and glycerol monolaurate (GML) interact with SLBs and cause membrane morphological changes under acidic pH conditions that are representative of the human skin surface. Although LA induces tubule formation under neutral pH conditions, we discovered that LA causes membrane phase separation under acidic pH conditions. By contrast, GML induced membrane budding in both pH environments, although there was more extensive membrane remodeling under acidic pH conditions. We discuss these findings in the context of how solution pH affects the ionization states and micellar aggregation properties of LA and GML as well as its effect on the bending stiffness of lipid bilayers. Collectively, the findings demonstrate that solution pH plays an important role in modulating the interaction of fatty acids and monoglycerides with phospholipid membranes, and hence influences the scope and potency of their membrane-disruptive activities.